2011
DOI: 10.1111/j.1464-410x.2011.10290.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate‐term oncological efficacy of laparoscopic retroperitoneal lymph node dissection for non‐seminomatous germ cell testicular cancer

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What’s known on the subject? and What does the study add? Other have reported that laparoscopic RPLND is feasible and safe when performed by skilled laparoscopic surgeons. We show that patients undergoing laparoscopic RPLND do not recur at the site of the lymph node dissection, even when chemotherapy is not given for nodal disease. This shows that laparoscopic RPLND is therapeutically effective in removing tumors that may have spread from the testicle to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Within the past 18 months, studies from centers performing minimally invasive RPLND with therapeutic intent (rather than for biopsy or staging) report node counts and intermediate-term recurrence rates replicating open surgical results [67,[70][71][72][73]. Hyams et al [67] report that 91 patients who underwent laparoscopic RPLND had intraoperative complication rates less than 5% and postoperative complication rates less than 10%.…”
Section: Testicular Cancermentioning
confidence: 99%
“…Within the past 18 months, studies from centers performing minimally invasive RPLND with therapeutic intent (rather than for biopsy or staging) report node counts and intermediate-term recurrence rates replicating open surgical results [67,[70][71][72][73]. Hyams et al [67] report that 91 patients who underwent laparoscopic RPLND had intraoperative complication rates less than 5% and postoperative complication rates less than 10%.…”
Section: Testicular Cancermentioning
confidence: 99%
“…The management of vascular surgical complication in L‐RPLND was a specific challenge and required superior skills in both laparoscopy and open RPLND in case conversion was necessary. Nevertheless, this procedure evolved with time and series reported longer follow up in larger number of patients where safe oncological outcomes were found while maintaining low morbility and faster recovery from the procedure . For example, Hyams et al reported 3 year follow up of a large single institutional cohort and demonstrated safe oncological outcomes.…”
Section: Evolution and Laparoscopic Rplndmentioning
confidence: 99%
“…Although L-RPLND appears to be safe and confers diagnostic and therapeutic benefits to patients, more cases and longer follow-ups are needed to confirm this 14 . Unfortunately, due to patient sample constraints, there are very few studies comparing O-RPLND with L-RPLND for perioperative outcomes in TGCTs 15 .…”
Section: Introductionmentioning
confidence: 98%